Disinformasi Berbasis Artificial Intelligence dan Krisis Kepercayaan Publik dalam Information Warfare pada Konflik Iran–As–Israel 2026: Perspektif Hukum Siber dan Hukum Pidana Internasional - Tomi Agi Fratama; Priskila Kurniawati (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The development of Artificial Intelligence (AI) has significantly enhanced the creation and dissemination of disinformation in international conflicts. The escalation of the 2026 Iran–U.S.–Israel conflict demonstrated the use of synthetic content, deepfakes and digital information manipulation as instruments of information warfare. This study aims to analyze the legal status of AI-based disinformation from the perspectives of cyber law and international criminal law. The research employs a normative legal method using statutory, conceptual and case approaches. The findings indicate that AI-based disinformation has not yet been recognized as a distinct criminal offense under international law. From a cyber law perspective, the use of AI to disseminate disinformation may be associated with cybercrime if it fulfills the elements of specific cyber offenses. Furthermore, international criminal law provides the possibility of liability when disinformation is used to support or facilitate the commission of international crimes within the jurisdiction of the Rome Statute.